Transsacral Osseous Corridor Anatomy Is More Amenable To Screw Insertion In Males: A Biomorphometric Analysis of 280 Pelves. Issue 10 (October 2016) - Gras, Florian; Gottschling, Heiko; Schröder, Manuel; Marintschev, Ivan; Hofmann, Gunther O.; Burgkart, Rainer
Abstract: Background: Percutaneous iliosacral screw placement is the standard procedure for fixation of posterior pelvic ring lesions, although a transsacral screw path is being used more frequently in recent years owing to increased fracture‐fixation strength and better ability to fix central and bilateral sacral fractures. However, biomorphometric data for the osseous corridors are limited. Because placement of these screws in a safe and effective manner is crucial to using transsacral screws, we sought to address precise sacral anatomy in more detail to look for anatomic variation in the general population. Questions/purposes: We asked: (1) What proportion of healthy pelvis specimens have no transsacral corridor at the level of the S1 vertebra owing to sacral dysmorphism? (2) If there is no safe diameter for screw placement in the transsacral S1 corridor, is an increased and thus safe diameter of the transsacral S2 corridor expected? (3) Are there sex‐specific differences in sacral anatomy and are these correlated with known anthropometric parameters? Methods: CT scans of pelves of 280 healthy patients acquired exclusively for medical indications such as polytrauma (20%), CT angiography (70%), and other reasons (10%), were segmented manually. Using an advanced CT‐based image analysis system, the mean shape of all segmented pelves was generated and functioned as a template. On this template, the cylindric transsacral osseous corridor at the level of the S1 and S2 vertebrae was determined manually. Each pelvis then was registered to the template using a free‐form registration algorithm to measure the maximum screw corridor diameters on each specimen semiautomatically. Results: Thirty of 280 pelves (11%) had no transsacral S1 corridor owing to sacral dysmorphism. The average of maximum cylindrical diameters of the S1 corridor for the remaining 250 pelves was 12.8 mm (95% CI, 12.1‐13.5 mm). A transverse corridor for S2 was found in 279 of 280 pelves, with an average of maximum cylindrical diameter of 11.6 mm (95% CI, 11.3‐11.9 mm). Decreasing transsacral S1 corridor diameters are correlated with increasing transsacral S2 corridor diameters (R value for females, −0.260, p < 0.01; for males, −0.311, p < 0.001). Female specimens were more likely to have sacral dysmorphism (defined as a pelvis without a transsacral osseous corridor at the level of the S1 vertebra) than were male specimens (females, 16%; males, 7%; p < 0.003). Furthermore female pelves had smaller‐corridor diameters than did male pelves (females versus males for S1: 11.7 mm [95% CI, 10.6‐12.8 mm] versus 13.5 mm [95% CI, 12.6‐14.4 mm], p < 0.01; and for S2: 10.6 mm [95% CI, 10.1‐11.1 mm] versus 12.2 mm [95% CI, 11.8‐12.6 mm ], p < 0.0001). Conclusions: Narrow corridors and highly individual, sex‐dependent variance of morphologic features of the sacrum make transsacral implant placement technically demanding. Individual preoperative axial‐slice CT scan analyses and orthogonal coronal and sagittal reformations are recommended to determine the prevalence of sufficient‐sized osseous corridors on both levels for safe screw placements, especially in female patients, owing to their smaller corridor diameters and higher rate of sacral dysmorphism.